2009
DOI: 10.1271/bbb.90319
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Specific Procedure to Permeabilize the Plasma Membrane ofSchizosaccharomyces pombe

Abstract: Cu(2+)-treatment is a useful technique in selectively permeabilizing the fungal plasma membrane. We describe herein a practical application with Schizosaccharomyces pombe. Incubation of cells with 0.5 mM CuCl(2) at 30 degrees C for 20 min induced efficient leakage of cytosolic constituents. The kinetic characteristics of the calcium and amino acid flux from Cu(2+)-treated S. pombe cells suggested that the Cu(2+) treatment permeabilized the plasma membrane without loss of vacuolar function. As a further applica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The S . pombe wild-type, avt3 Δ, and avt3 Δ/pTN54- avt3 + cells were cultured in MM medium without thiamine, and vacuolar amino acid pools were prepared using the cupric ion method [33]. As shown in Table 1, the vacuolar levels of threonine, serine, asparagine, glutamine, glycine, alanine, and proline, as well as basic amino acids (histidine, arginine, and lysine), were obviously increased in the avt3 Δ cells compared with the wild-type cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The S . pombe wild-type, avt3 Δ, and avt3 Δ/pTN54- avt3 + cells were cultured in MM medium without thiamine, and vacuolar amino acid pools were prepared using the cupric ion method [33]. As shown in Table 1, the vacuolar levels of threonine, serine, asparagine, glutamine, glycine, alanine, and proline, as well as basic amino acids (histidine, arginine, and lysine), were obviously increased in the avt3 Δ cells compared with the wild-type cells.…”
Section: Resultsmentioning
confidence: 99%
“…pombe and S . cerevisiae [33,34]. The amino acid contents in the fractions were analyzed with an amino acid analyzer (Hitachi L-8800).…”
Section: Methodsmentioning
confidence: 99%
“…1,2) Vacuolar accumulation of basic amino acids has been reported in several fungal species, [17][18][19] implicating that it is a common feature among fungi. Under nitrogen starvation, basic amino acids (Table 2) as well as other amino acids (data not shown) rapidly disappeared from vacuoles, suggesting the existence of export system(s).…”
Section: Discussionmentioning
confidence: 99%
“…5) In the fission yeast Schizosaccharomyces pombe, there are also large amounts of basic amino acids compartmentalized in the vacuoles, and small but significant amounts of acidic amino acids are retained in the organelles. 6) Our reverse genetics study suggested that Fnx1p and Fnx2p of S. pombe, two Vba2p homologs, are involved in the vacuolar uptake of lysine and isoleucine. 7) Based on phylogenetic analysis of the S. cerevisiae and S. pombe genome databases, we found homologs of S. cerevisiae AVT members, Avt3p and Avt5p, in S. pombe.…”
mentioning
confidence: 85%